HOW TO IMPROVE STUDENTS’ METACOGNITIVE SKILLS THROUGH WRITING A REFLECTION DIARY? - Дәрібай, П.Д.; Көлдеев, С.Б. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The students in our study repeatedly had to reflect on how and what they have learned as the units unfolded, and received continuous feedback from their teachers on their performances. The purposes of the present study is to evaluate whether reflection journal writing was effective in promoting self-reflection and metacognitive skills, and whether students become better at self-reflection if they engage continuously in reflection journal writing. 12 students of Nazarbayev intellectual school in Kyzylorda(5 female,7 male) were participated on research. Each student has his own reflection notebook (diary)and are keeping notes at the end of each lesson. Data was collected twice, once at the beginning and again towards the end of terms. Outcomes of the textual content analyses revealed that students reflected on both the process and contents of their learning: critical review of past learning experiences, learning strategies and summaries of what was learned and it’s positive effect on metacognitive skills and academic performance in general.
Keywords: Self-reflection diary; metacognition; academic performance